IMAGE TRANSFORMATION OF PETER THE FIRST IN HISTORICAL VIEWS OF RUSSIAN EMPERORS DURING XVIII - XIX CENTURY - Tat’yana Aidunova (Гуманитарные и юридические исследования)
The article studies image transformation of Peter I in historical views of Russian rulers during XVIII-XIX century. The author analyzes factors, instruments and methods of modeling Peter I's image by using various sources. According to Maurice Halbwachs' theory, the author explains the transformation of Peter I's image connected with foreign and inner policy tasks, implemented by the Russian Emperor. In the conclusion the author dwells on the special place of Peter I in memorial culture of Russian rulers during XVIII-XIX century. There are some cases in history when the ruler continued to have an impact on the society after the transfer the board to the heirs. One of such examples, of course, is the first Russian emperor Peter I. The Emperor's acts were so great that they could go unnoticed by the future monarchs. Even today, the image of the one who "cut through the window to Europe" is not left behind, discussions about his personality take place in the scientific, common and even political and ideological space. The evaluations of his personality could not be objective, but this does not prevent the author from tracing the factors, mechanisms and forms of forms the image of Peter I with a wide range of sources. As the author observes, respectful attitude towards Peter I during the 18th century can be explained from the point of view of genetic bonds. Most notably, the first successor of Peter the Great immortalized his image in the cultural heritage of the Russian Empire. The author notices the change in the paradigm of the perception of Peter I beginning with Alexander II, who had to think not of strengthening the principles of the autocracy, but of meeting the society needs to participate in social and political life and influence the fate of the country. Emperor Alexander III differed from Peter I as regards the key direction of the domestic policy and cultural-historical ideal. Speaking about the last monarch of the Romanovs family, the author assures that he had a negative attitude to the methods of domestic policy of its first Emperor, aimed at Europeanization, rather than to the europeanization of Russia.